Farm Family Support in Increasing Health Awareness - Enggal Hadi Kurniyawan; Malikal Balqis; Muhammad Irfan Aditya Pratama; Harum Putri Permata Hati; Onny Ega Isfadillah; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur (Health and Technology Journal (HTechJ), 2023)
Health problems such as under-five nutrition, exclusive breastfeeding, breast examination, and adherence to taking TB medication in children have become a global concern to increase awareness of the health of farming family members. Low health among farming families is often caused by low family support. This can lead to an increased risk of severe health conditions and diseases and affect the overall quality of life and well-being of farming family members. Therefore, family support is needed to improve family health status. This study aims to analyze support farming families for health awareness. The method used in this study was a literature review article from article search engines such as PubMed, Google Scholar, and Science Direct, which was analyzed using the PRISMA technique by including articles published in the last five years. The study results show that the support of the farming family is very influential on health awareness. Family support is very influential on health awareness. Family support can increase family awareness to improve nutrition, comply with treatment, realize the importance of exclusive breastfeeding for babies, and be able to do regular health checks. Action and education are needed to improve social functions and family communication, increase family support, and encourage better family health awareness.